2003
DOI: 10.1099/vir.0.19271-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus cores are transported on microtubules

Abstract: Infection with Vaccinia virus (VV) produces several distinct virions called intracellular mature virus (IMV), intracellular enveloped virus (IEV), cell-associated enveloped virus (CEV) and extracellular enveloped virus (EEV). In this report, we have investigated how incoming virus cores derived from IMV are transported within the cell. To do this, recombinant VVs (vA5L-EGFP-N and vA5L-EGFP-C) were generated in which the A5L virus core protein was fused with the enhanced green fluorescent protein (EGFP) at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 51 publications
5
93
1
Order By: Relevance
“…Potential candidates are microtubules that have been reported to be organised in an orientation compatible with their use as tracks for migration of NCDs (Brown and Lemmon, 2001). However, the speed of migration of NCDs is at least 50 times slower than the speed recorded for migration of organelles along microtubules (Pollock et al, 1998;Carter et al, 2003). Alternatively, actin filaments may be suitable candidates, although no actin cable was reported at the posterior pole of endosperm in Coronopus didymus, a relative of Arabidopsis (Nguyen et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Potential candidates are microtubules that have been reported to be organised in an orientation compatible with their use as tracks for migration of NCDs (Brown and Lemmon, 2001). However, the speed of migration of NCDs is at least 50 times slower than the speed recorded for migration of organelles along microtubules (Pollock et al, 1998;Carter et al, 2003). Alternatively, actin filaments may be suitable candidates, although no actin cable was reported at the posterior pole of endosperm in Coronopus didymus, a relative of Arabidopsis (Nguyen et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…19 We used a vaccinia strain with Green Fluorescent Protein (GFP) fused to the viral A5L protein, a DNA packaging protein that is one of the most abundant within the viral particle. 20 As such, it is possible to detect single viral particles by fluorescence microscopy or flow cytometry. This virus was used along with 7-amino-actinomycin staining to assess the relative levels of initial infection and the position in the cell cycle of HCT-116 cells alone or following paclitaxel treatment (as determined 2 h after addition of the virus, before the viral infection itself can affect the position of the cells in the cell cycle).…”
Section: Paclitaxel Synergizes With Oncolytic Vaccinia Virus In Vitromentioning
confidence: 99%
“…35 The WR strain containing an A5L-GFP fusion was provided by Geoff Smith (Imperial College, London, UK). 20 …”
Section: Cell Lines and Vaccinia Strainsmentioning
confidence: 99%
“…The morphogenesis of RGV showed that virus particles assembled in the viromatrix (Zhang et al, 1999(Zhang et al, , 2001(Zhang et al, , 2002. Studying the ultrastructure of viromatrix contributes to understanding the assembly pathway and pathogenesis (Granzow et al, 1997;Wolf et al, 2000;Griffiths et al, 2001;Qin et al, 2001;Chao et al, 2004), and the relationships between the viromatrix and cellular components, such as the cytoskeleton (Hollinshead et al, 2001;Carter et al, 2003), mitochondria (Rojo et al, 1998) and the endoplasmic reticulum (ER) (Sodeik et al, 1993;Risco et al, 2002), have provided impor-tant insights into virus assembly. The viromatrix of large DNA viruses had been investigated in detail by electron microscopy, for example, African swine fever virus (ASFV) and vaccinia virus (VV) (Andres et al, 1998;Rouiller et al, 1998;Griffiths et al, 2001).…”
Section: Introductionmentioning
confidence: 99%